2021
DOI: 10.1177/15266028211038593
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Transplant Renal Artery Stenosis: A Systematic Review and Meta-analysis

Abstract: Objective Endovascular treatment through either percutaneous transluminal angioplasty (PTA) alone or stenting has been previously used as a treatment for transplant renal artery stenosis (TRAS). This review aimed to investigate the results of endovascular treatment for renal artery stenosis in transplanted kidneys as compared with the outcomes of interventions, medical management, and graft survival in non-TRAS patients. Methods A systematic review of PubMed, Google Scholar, Cochrane, and Scopus was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 87 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Many of these complications can be treated by interventional radiologic procedures. Still, the restenosis rate is between 12-28% ( 11 , 12 ).…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…Many of these complications can be treated by interventional radiologic procedures. Still, the restenosis rate is between 12-28% ( 11 , 12 ).…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…Concerning transplant renal artery stenosis, a recent metaanalysis concluded that the endovascular treatment improves graft preservation, renal function, overall blood pressure, and the use of medications [14].…”
Section: Introductionmentioning
confidence: 99%